Implementing Serious Illness Communication Processes in Primary Care: A Qualitative Study. (May 2021) - Paladino, Joanna; Brannen, Elise; Benotti, Emily; Henrich, Natalie; Ritchie, Christine; Sanders, Justin; Lakin, Joshua R.
Purpose: Primary care clinicians face barriers to engaging patients in conversations about prognosis, values, and goals ("serious illness conversations"). We introduced a structured, multi-component intervention, the Serious Illness Care Program (SICP), to facilitate conversations in the primary care setting. We present findings of a qualitative study to explore practical aspects of program implementation. Methods: We conducted semi-structured interviews of participating primary care physicians, nurse care coordinators, and social workers and coded transcripts to assess the activities used to integrate SICP into the workflow. Results: We conducted interviews with 14 of 46 clinicians from 6 primary care clinics, stopping with thematic saturation. Qualitative analysis revealed major themes around activities in the timing of the conversation (before, during, and after) and overarching insights about the program. Clinicians used a variety of strategies to adapt program components while preserving key program goals, including processes to generate accountability to ensure that conversations happen in busy clinical workflows. The interviews revealed changes to clinicians' mindset and norms, such as the recognition of the need to start conversations earlier in the illness course and the use of more expansive models of prognostic communication that address function and quality of life. Data also revealed indicators of sustainable behavior change and the spread of communication practices to patients outside the intended program scope. Conclusion: SICP served as a framework for primary care clinicians to integrate serious illness communication into routine care. The shifts in processes employed by inter-professional clinicians revealed comprehensive models for prognostic communication and creative workflows to ensure that patients with complex illnesses had proactive, longitudinal, and patient-centered serious illness conversations and care planning.